Adopt FERPA Basics training test questions for staff and work‐study students. Issue 3 (May 2016) - Rainsberger, Richard
Abstract : Last month, we looked at 10 Family Educational Rights and Privacy Act test questions for faculty (using Bloom's Taxonomy). This month, you have 12 questions, again using Bloom's Taxonomy, designed for staff and work‐study students.